EDUKASI PERTOLONGAN PERTAMA PADA KECELAKAAN SEPEDA DAN BHD NON-MEDIS BAGI KOMUNITAS SEPEDA PROVINSI KALIMANTAN BARAT - UR Hidayat; N Nurpratiwi; A Akbar; F Alfikrie (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Abstract: The most cases of cardiac arrest are cases outside the hospital. Education in certain communities about true Basic Life Support is necessary because communities can be first responder and agents of change. One of the communities that is required to be able to do first aid is the bicycle community because lately there are many phenomena of cardiac arrest events and accidents among this community. In order to be able to do initial assistance on the scene quickly and appropriately, of course community members must have sufficient knowledge. Therefore, it is necessary activities to educate the community, especially the bicycle community. The method of activity consists of pre-test, interactive lectures as well as demostration, followed by simulation of Basic Life Support of Heart and Trauma, terminated post test. The result of the activities obtained that education can increase knowledge. Proven before education most (71%) participants' knowledge was low, and after education the participants' knowledge increased to (62%) in high categories. It is important to provide more emergency education to other communities in the community.